Permeability of Dental Adhesives – A SEM Assessment - Malacarne-Zanon, Juliana; de Andrade e Silva, Safira M.; Wang, Linda; de Goes, Mario F.; Martins, Adriano Luis; Narvaes-Romani, Eliene O.; Anido-Anido, Andrea; Carrilho, Marcela R.O. (European Journal of Dentistry, 2010)
Objectives: To morphologically evaluate the permeability of different commercial dental adhesives using scanning electron microscopy.Methods: Seven adhesive systems were evaluated: one three-step system (Scotchbond Multi- Purpose - MP); one two-step self-etching primer system (Clearfil SE Bond – SE); three two-step etch-and-rinse systems (Single Bond 2 – SB; Excite – EX; One-Step – OS); and two single-step selfetching adhesives (Adper Prompt – AP; One-Up Bond F – OU). The mixture of primer and bond agents of the Clearfil SE Bond system (SE-PB) was also tested. The adhesives were poured into a brass mold (5.8 mm x 0.8 mm) and light-cured for 80 s at 650 mW/cm2. After a 24 h desiccation process, the specimens were immersed in a 50% ammoniac silver nitrate solution for tracer permeation. Afterwards, they were sectioned in ultra-fine slices, carbon-coated, and analyzed under backscattered electrons in a scanning electron microscopy.Results: MP and SE showed slight and superficial tracer permeation. In EX, SB, and OS, permeation extended beyond the inner superficies of the specimens. SE-PB did not mix well, and most of the tracer was precipitated into the primer agent. In AP and OU, “water-trees” were observed all over the specimens.Conclusions: Different materials showed distinct permeability in aqueous solution. The extent of tracer permeation varied according to the composition of each material and it was more evident in the more hydrophilic and solvated ones. (Eur J Dent 2010;4:429-439)
Keywords: Dental adhesives; Hydrophilicity; Solvents; Nanoleakage